PENGARUH BERBAGAI JARAK TANAM DAN FREKWENSI PENYIANGAN TERHADAP PERTUMBUHAN DAN PRODUKSI WORTEL (Daucus Carota L.) - Lyndon Parulian Nainggolan; Donatus Dahang; Nani Kitti Sihaloho; Chaula Lutfia Saragih; Lenni Marlina Pasaribu (Universitas Quality, 2023)
Research on the effect of plant spacing and weeding time on the growth and production of carrots (Daucus carota L) has been well carried out in February-May 2021 at UPT. Kutagadung Horticulture Parent Seeds. Berastagi District, Karo Regency, North Sumatra. The aim of the study was to determine the effect of spacing and weeding time on the growth and yield of carrots. The results showed that the average plant height affected by the distance between J1 18.5 cm and J2 16.4 cm and J3 15.2. cm and the average height of the influence of weeding, namely M0 (17 cm) was significantly different from M1 (16.5 cm), M2 (16.6 cm), and M4 (16.5 cm). The effect of spacing (J) on tuber length showed that J1 (17.51 cm) was significantly different from J2 (18.22 cm) and J3 (18.23 cm). The effect of spacing (J) treatment on tuber diameter showed that J1 (3.36 cm) was significantly different from J2 (3.79 cm), and significantly different from J3 (5.27 cm), the effect of weeding time (M0) 3, 52 cm was significantly different from M1 (4.14 cm), M2 (4.25 cm), M3 (4.34 cm), and M4 (4.47 cm), and the combination treatment J1M0 resulted in the smallest tuber size of 3.1 cm. and the largest in J3M4 is 5.75 cm. The combination of J3M4 produced the highest tuber diameter of 5.75 cm which was the optimum treatment. The effect of plant spacing on tuber weight per sample was found that J1 (86.47 gr) was significantly different from J2 (101.82 gr) and J3 (186.48 gr), the effect of the weeding time factor M0 (70.24 gr) was significantly different from M1 (135.41 gr), M2 (137 gr), M3 (137.88), and M4 (144.08 gr)